Aggregation and Aggregation Biases in Production Functions: A Panel Data Analysis of Translog Models - Erik Biørn; Terje Skjerpen (Statistics Norway, Research Department, 2002)
An applied econometric study of aggregation, based on an unbalanced panel data set for manu-facturing plants is presented. Panel data are informative in examining aggregation of variables, parameters, and relationships empirically since they (i) allow estimation at both the micro and the macro level, and (ii) enable comparison of the time series properties of the exactly aggre- gated micro relationships with those obtained by performing aggregation by analogy. Numerical aggregation of Translog production functions for three manufacturing industries is considered. We show, under linear aggregation of inputs and output, that departures between geometric and arithmetic means of the inputs and correlation between the log-inputs, both their levels and time paths, contribute substantially to aggregation biases in the output volume and instability of the derived input and scale elasticities. Hence, the existence and stability of an approximate "macro Translog production function" over time can be questioned.
Keywords: C23; C43; D21; E23; L11; L60; 330; Aggregation. Panel Data. Translog. Scale elasticity. Input distribution.